2006
DOI: 10.1111/j.1460-9568.2006.04805.x
|View full text |Cite
|
Sign up to set email alerts
|

Clearance and prevention of prion infection in cell culture by anti‐PrP antibodies

Abstract: Prion diseases are transmissible and invariably fatal neurodegenerative disorders associated with a conformational transformation of the cellular prion protein (PrP C ) into a self-replicating and proteinase K (PK)-resistant conformer, scrapie PrP (PrP Sc ). Humoral immunity may significantly prolong the incubation period and even prevent disease in murine models of prionoses. However, the mechanism(s) of action of anti-PrP monoclonal antibodies (Mabs) remain(s) obscure. The murine neuroblastoma N2a cell line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 62 publications
(107 reference statements)
2
103
1
Order By: Relevance
“…Importantly, two of these regions (23-31 and 95-125) overlap with those that we have shown here to be critical for the functional activity of PrP C , as determined by the DBCA and patch clamp measurements. Ligands (GAGs and monoclonal antibodies) that bind to these two regions have been shown to inhibit PrP Sc formation in vitro and in vivo (16,68,69). Strikingly, we have found that some of these same ligands (e.g.…”
Section: Common Structural Domains Control Both the Functional Activimentioning
confidence: 68%
See 1 more Smart Citation
“…Importantly, two of these regions (23-31 and 95-125) overlap with those that we have shown here to be critical for the functional activity of PrP C , as determined by the DBCA and patch clamp measurements. Ligands (GAGs and monoclonal antibodies) that bind to these two regions have been shown to inhibit PrP Sc formation in vitro and in vivo (16,68,69). Strikingly, we have found that some of these same ligands (e.g.…”
Section: Common Structural Domains Control Both the Functional Activimentioning
confidence: 68%
“…Western Blotting and Immunofluorescence Staining-Western blots were probed with anti-PrP antibodies 6D11 (16) or 6H4 (17) followed by goat anti-mouse IgG (Pierce) and developed with ECL (GE Healthcare). Some of the samples in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Western Blotting and Immunofluorescence Staining-Western blots were probed with anti-PrP antibody 6D11 (18) and goat anti-mouse IgG (Pierce) and developed with ECL (GE Healthcare). Samples for each blot were normalized for total protein following measurement with the BCA protein assay (Pierce).…”
Section: It Has Been Proposed That Interactions With Prpmentioning
confidence: 99%
“…Alternatively, PrP in S and P fractions was immunoprecipitated with 15B3 or motif-grafted antibodies, as described below. Western blots were developed with anti-PrP antibodies 6D11 (Pankiewicz et al 2006) or 8H4 (Zanusso et al 1998) using the enhanced chemiluminescent detection system (Amersham Biosciences, Piscataway, NJ, USA).…”
Section: Cultured Cellsmentioning
confidence: 99%